A kind of high transparent PET sheet and preparation method thereof

By doping the ASA of the transformed temperature in PET, the acidic anhydrials, and the low -glass transformation temperature, the traditional PET materials have been solved in terms of both softness, transparency and strength, and achieved high -performance PET sheets.

CN118813012BActive Publication Date: 2025-01-28DESU TECH (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411297593.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-28
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Traditional PET materials have challenges in taking into account high flexibility, high transparency and high strength, especially after adding inorganic fillers, it is difficult to take into account both transparency and strength.

Method used

By mixed with polymide and acidic anhydrials in PET, the ASA with low glass transformation temperature is added, and the crystallization process of the material is adjusted to improve the softness and compatibility, while maintaining high transparency and intensity.

Benefits of technology

It realizes the good performance of PET sheets in terms of softness, transparency and strength, has good bending performance, and can add other additives to further improve the nature of the material as needed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of plastic materials, and in particular to a highly transparent PET sheet and a preparation method thereof. By designing a combination system of PET, polyolefin, and ASA and controlling the relationship between the glass transition temperature of ASA and the melting point of polyolefin, a PET sheet having high softness, high transparency, and high strength is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of plastic materials, and in particular to a highly transparent PET sheet and a preparation method thereof. Background Art

[0002] PET, or polyethylene terephthalate, also known as polyester resin, is a widely used resin material. Generally, it has good heat resistance, stiffness and mechanical properties. At the same time, it has good light transmittance without adding fillers or other components. It is widely used in films, sheets, packaging and other fields.

[0003] Normally, pure PET has good transparency and good strength without adding other inorganic fillers. However, PET has a problem. It is hard and generally compatible with other soft materials (such as polyethylene, EVA, etc.). Adding inorganic fillers will affect the overall transparency and strength, making it difficult to obtain sheets with high bending performance and high transparency. In order to improve transparency, inorganic fillers are usually not added to the system, which also makes it difficult for the coupling agents (such as silane coupling agents) traditionally used to improve the strength of PET to work, resulting in fewer methods to improve the strength of the material. Summary of the invention

[0004] The object of the present invention is to provide a PET sheet having high softness, high transparency and high strength.

[0005] First, the present application provides a highly transparent PET sheet, which comprises the following components in parts by mass:

[0006] 100 parts of PET raw material;

[0007] 20-40 parts of polyolefin;

[0008] 5-10 parts of anhydride grafted polyolefin;

[0009] ASA 5-10 parts;

[0010] The density of the polyolefin is not greater than 0.93 g / cm 3 ;

[0011] The glass transition temperature of the ASA is lower than the melting point of the PET, and the difference between the glass transition temperature of ASA and the melting point of polyolefin is no more than 10°C.

[0012] In the above method, the overall softness is improved by doping some polyolefin in PET. Since the polyolefin with lower density has a certain branched structure and lower molecular weight, it is not easy to form a chain structure in the system, nor is it easy to form a neatly arranged crystal form, so the softness of the system can be effectively improved. At the same time, in order to improve the compatibility between polyolefin and PET, avoid excessive loss in strength, and avoid the loss of transparency and strength caused by uneven orientation inside the material, anhydride grafted polyolefin is also added as a compatibilizer in this scheme.

[0013] Although anhydride grafted polyolefin is added, the molding performance of polyolefin itself is poor, especially the polyolefin with low density will cause obvious loss of strength of the system, and because PET has a high melting point, its processing temperature is usually high, which makes the overall crystallization performance poor, and the system formed during co-processing has poor transparency. Therefore, ASA is additionally added in this scheme. ASA can be used to improve compatibility on the one hand, so that polyolefin and PET can form a more uniform phase in the system, and on the other hand, ASA itself does not reduce the softness of the system. In the selection of ASA, an ASA system with a glass transition temperature lower than the melting point of PET is selected, and the glass transition temperature of ASA is controlled to be close to the melting point of polyolefin, so that during the molding process of the material, ASA will not quickly form a glass state, but wait for PET to solidify first, and then undergo a glass transition. In this process, the glass transition temperature of ASA and the solidification of polyolefin are carried out simultaneously, which can better form a homogeneous phase in the system, which not only prevents the overall hardness of the material from occurring, improves softness, but also reduces crystal agglomeration in the system and improves transparency.

[0014] On the whole, the above materials have good performance in softness, transparency and strength, and the sheets made therefrom have good bendability.

[0015] In addition, in the above scheme, other additives may be added, for example, antioxidants, anti-aging agents, etc. may be added to improve the overall properties. The above materials may be added according to the properties of the purchased raw materials. Generally, the amount of each additive added should not exceed 5% of the total mass.

[0016] Preferably, the melting point of the polyolefin is not higher than 113°C.

[0017] The use of polyolefins with lower melting points can better promote the improvement of softness and toughness, and also has better fluidity. Under the action of ASA, even polyolefins with low melting points can be well compatible with PET in the system.

[0018] Preferably, the anhydride grafted polyolefin is maleic anhydride grafted LLDPE, whose lower density can better reduce hardness and improve softness and bendability.

[0019] Preferably, the raw material also includes EVA, and the mass proportion of the EVA is 5 to 10 parts. Further preferably, the vinyl acetate content of the EVA is 40 to 60%.

[0020] In the above scheme, the bending resistance of the system is further improved by adding EVA. EVA has a soft ethylene olefin segment and a non-reactive terminal branch. The ester group on the branch provides a hydrogen bond binding area, so that the system as a whole maintains good softness and is not prone to cracks after multiple bending, thereby improving the overall mechanical properties of the sheet.

[0021] Preferably, the cellulose or cellulose derivative is 2 to 4 parts by weight. Further preferably, the cellulose or cellulose derivative is hydroxypropyl methylcellulose ester. Further preferably, the hydroxypropyl methylcellulose ester is specifically HPMCAS. Further preferably, the HPMCAS has an acetyl content of 8% and a succinyl content of not less than 5%.

[0022] In the above scheme, cellulose or cellulose derivatives are added, which can exist as a compatibilizer to improve the uniformity of the system and the fluidity of the system. Cellulose ether itself has amphiphilic properties and relatively low viscosity, while cellulose has a higher viscosity. In comparison, the addition of cellulose ether improves the fluidity and uniformity of the system, and the overall transparency is higher. Furthermore, HPMCAS with an acetyl content of 8% and a succinyl content of not less than 5% can better balance the strength and transparency of the PET system without compromising the puncture resistance of the system. In addition, the present application also relates to the above-mentioned high-transparency PET sheet, in which the raw materials are mixed and heated to flow, and formed by at least one method of extrusion, injection molding, casting, and calendering.

[0023] In summary, in the present application, polyolefin is added to the system to improve the softness of the system, and anhydride grafted polyolefin and ASA system are added to the system. The property of ASA having a lower melting point than PET is utilized to adjust the overall crystallization process, so that the system has good softness and the distribution of each phase is relatively uniform, thereby having good uniformity, transparency and mechanical strength. DETAILED DESCRIPTION

[0024] The scheme in this application is further explained through the following specific implementation methods.

[0025] In the following examples, the prepared samples were tested by the following method.

[0026] 1. Transparency: Determine the haze according to GB2410-2008.

[0027] 2. Flexibility: Refer to IS0178-2010 to measure the flexural modulus of the product.

[0028] 3. Impact resistance: Referring to GB / T 9639.1-2008 (B), the sample was prepared into a 0.3 mm thick film and its impact resistance at 20°C was measured.

[0029] 4. Tensile strength: refer to GB / T1040.1-2018 to measure the tensile strength at 20°C.

[0030] For the following examples, the preparation methods used are as follows:

[0031] After mixing the components, they are extruded into the mold through a twin-screw extruder and then injection molded. The temperature of the extruder is 255°C. It should be noted that the temperature can be adjusted to a certain extent according to the performance of the material itself. This adjustment is a routine adjustment. The technicians can design the most suitable processing temperature according to the actual product status.

[0032] Example 1. In this example, the role of polyolefin and ASA in the system is studied. Specifically, in this example, different polyolefins and elastomers are used, and the masses of polyolefin and ASA are fixed to determine their effects in the system.

[0033] In this embodiment, the materials are selected as follows:

[0034] PET raw material, using commercial bottle-grade PET, melting point 252 ° C, relative mass parts 100;

[0035] The anhydride grafted polyolefin is maleic anhydride grafted LLDPE, with a relative weight portion of 10 parts;

[0036] Polyolefin, as shown in Table 1, the relative mass parts are 30 parts;

[0037] Elastomer component, as shown in Table 2, the relative mass parts are 10 parts;

[0038] The polyolefins used in this example are shown in Table 1.

[0039]

[0040] The above materials are all injection molding grade. It should be noted that among the above raw materials, if the masterbatch contains antioxidants, antioxidants, etc., no additional addition is required. If the masterbatch does not contain antioxidants, antioxidants, etc., it is necessary to add antioxidants or process under inert gas. The type and amount of antioxidants added are conventional operations in the industry and will not be repeated in the following examples.

[0041] The elastomers selected in this embodiment are shown in Table 2.

[0042]

[0043] It should be noted that for the above elastomers, some materials have more than one glass transition temperature, and the above glass transition temperatures all refer to the highest glass transition temperature.

[0044] The above materials were combined and prepared into samples, and the obtained experimental groups and experimental results are shown in Table 3.

[0045]

[0046] In the above experiments, it can be clearly seen that a variety of polyolefins can effectively reduce the bending modulus of the system, but whether other properties can be maintained requires further study. Specifically, among the various polyolefins, the bending modulus of the two types of polyolefins P1 and P4 is reduced less, and the overall performance is not good. The reason may be that the high-density polyolefin has a small effect on reducing the softness of the system, cannot achieve a soft effect, and has poor impact resistance.

[0047] When other polyolefins are selected, experiments are first conducted on six elastomers A1 to A6. It can be seen that, on the whole, in the experimental group using ASA, the system has good mechanical strength and high transparency, and on the whole, the greater the gap between the glass transition temperature of the elastomer and the melting point of the polyolefin, the worse the overall mechanical properties and transparency. This may be related to the uneven crystallization during the molding process, that is, when the glass transition temperature of ASA is close to the melting point of the polyolefin, the glass transition of ASA and the molding of the polyolefin are carried out simultaneously, so a more uniform structure can be formed, and materials with lower glass transition temperatures such as polyurethane cannot achieve the glass transition process in the system. Although its overall softness is improved to a certain extent and the modulus is slightly reduced, due to the insufficient support strength in the system, its impact resistance and tensile properties are reduced, and it cannot meet the mechanical property requirements as a sheet as a whole. For materials such as SBS, which has a relatively low glass transition temperature, if its glass transition temperature is lower than the melting point of polyolefin, then if it undergoes glass transition after the polyolefin is formed, the system will tend to become brittle, and the impact resistance and transparency will be reduced.

[0048] Furthermore, it can be seen that compared with other polyolefins, the softness and mechanical properties of the final products of P2, P3, P6 and P10 have certain advantages, proving that materials with lower melting points can form a softer system in the system, while improving the uniformity of the system and having better effects as additives.

[0049] On the basis of Example 1, further experiments were conducted on Experimental Groups 1-6, and the addition amounts of polyolefin and ASA in the system were adjusted. The results are shown in Table 4.

[0050]

[0051] From the above experimental data, it can be seen that, overall, the more polyolefin is added, the softer the system is, and the worse the impact strength is. The haze begins to increase after the polyolefin addition exceeds 40 parts. This shows that when the amount of polyolefin is too large, it is difficult to form a uniform system inside, which easily leads to a decrease in its transparency. The optimal amount of ASA added in the system is 5 to 10 parts. Too little will lead to a decrease in mechanical properties and poor transparency, while too much ASA will also lead to a decrease in transparency.

[0052] Embodiment 3, on the basis of embodiment 1-6, further add EVA, i.e. ethylene-vinyl acetate copolymer, the EVA added in this embodiment is commercially available, and the content of its vinyl acetate chain segment is 20%, 40%, and 60% respectively in terms of label number. Further increasing the content of vinyl acetate chain segment will lead to poor material forming performance, and its shaping effect is poor, which is no longer reflected in subsequent experiments. The purpose of this embodiment is to study the effect of adding different masses of various EVA in the system. The specific experimental results are shown in Table 5.

[0053]

[0054] It can be seen from the above experimental data that the addition of EVA can further improve the impact resistance and tensile strength of the system, and at the same time reduce the flexural modulus of the material to a certain extent without affecting the transparency. On the whole, the flexural modulus decreases with the increase of the amount of EVA added and the content of vinyl acetate monomer, but the overall strength will also increase first and then decrease with the amount of EVA added. On the whole, EVA should not be added to the system in excess of 10 parts by mass.

[0055] Example 4: Based on Examples 3-7, cellulose or cellulose derivatives are further added, wherein the selected cellulose derivatives include HPMCAS (hydroxypropyl methylcellulose acetate succinate), HPMC (hydroxypropyl methylcellulose) and HPMCP (hydroxypropyl methylcellulose phthalate), and their parameters are shown in Table 6.

[0056]

[0057] For HPMCAS, the ester content refers to the sum of the acetyl content and the succinyl content. Overall, the viscosity of the four HPMCAS is relatively close, so its effect on the mechanical properties of the system from the perspective of viscosity is relatively small.

[0058] After adding different types and amounts of cellulose or cellulose derivatives, the overall performance test of the material is shown in Table 7.

[0059]

[0060] From the above experimental data, it can be seen that after adding cellulose or cellulose derivatives, the haze of the system is further reduced, and the mechanical properties are improved to a certain extent. It is worth noting that in this embodiment, in order to maintain comparability with other embodiments, each group still uses the same processing temperature. In fact, after adding HPMCAS or HPMCP, the system can reduce the processing temperature to a certain extent.

[0061] For various HPMCAS, the acetyl and succinyl contents need to be controlled above a certain range, otherwise there will be a small adverse effect on the strength of the system, and it is also easy to make the system harder and the modulus increase. For HPMCP, the modulus of the system will be higher than that of HPMCAS after addition, which may be due to the increased material stiffness caused by the aromatic ring in the system.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly transparent PET sheet, characterized in that: The components are as follows according to mass parts: 100 parts of PET raw material; 20-40 parts of polyolefin; 5-10 parts of anhydride grafted polyolefin; ASA 5-10 parts; The density of the polyolefin is not greater than 0.93 g / cm 3 ; The glass transition temperature of the ASA is lower than the melting point of the PET, and the difference between the glass transition temperature of the ASA and the melting point of the polyolefin is no more than 10°C; The anhydride grafted polyolefin is maleic anhydride grafted LLDPE.

2. A highly transparent PET sheet according to claim 1, characterized in that: The melting point of the polyolefin is not higher than 113°C.

3. A highly transparent PET sheet according to claim 1, characterized in that: The raw material also includes EVA, and the mass proportion of the EVA is 5 to 10 parts.

4. A highly transparent PET sheet according to claim 3, characterized in that: The vinyl acetate content of the EVA is 40-60%.

5. The highly transparent PET sheet according to claim 1, characterized in that: It also includes 2 to 4 parts by weight of cellulose or cellulose derivatives.

6. A highly transparent PET sheet according to claim 5, characterized in that: The cellulose or cellulose derivative is selected from hydroxypropyl methylcellulose.

7. A highly transparent PET sheet according to claim 6, characterized in that: The hydroxypropyl methylcellulose ester is specifically HPMCAS.

8. A highly transparent PET sheet according to claim 7, characterized in that: The HPMCAS has an acetyl content of 8% and a succinyl content of not less than 5%.

9. A method for preparing the highly transparent PET sheet according to any one of claims 1 to 8, characterized in that: The raw materials are mixed and heated until fluidized, and then formed by at least one method selected from the group consisting of extrusion, injection molding, casting, and calendering.

Citation Information

Patent Citations

  • Polycarbonate / polyethylene glycol terephthalate resin composite and preparation method

    CN101812223A

  • PET (Polyethylene Terephthalate) high-transparency smooth master batch and production process thereof

    CN114921067A